2004
DOI: 10.1136/bmj.38309.664444.8f
|View full text |Cite
|
Sign up to set email alerts
|

Providing child safety equipment to prevent injuries: randomised controlled trial

Abstract: Objective To assess the effectiveness of safety advice and safety equipment in reducing unintentional injuries for families with children aged under 5 years and living in deprived areas. Design Randomised controlled trial. Setting 47 general practices in Nottingham. Participants 3428 families with children under 5. Intervention A standardised safety consultation and provision of free and fitted stair gates, fire guards, smoke alarms, cupboard locks, and window locks. Main outcome measures Primary outcome measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 22 publications
2
93
0
3
Order By: Relevance
“…27,28 However, even if these interventions prove to be effective, many children still get involved in poisoning accidents. [29][30][31] The fact is that, thus far, in countries such as Brazil, laws have not been sanctioned requiring the mandatory packaging with a protective cover for children:…”
Section: Discussionmentioning
confidence: 99%
“…27,28 However, even if these interventions prove to be effective, many children still get involved in poisoning accidents. [29][30][31] The fact is that, thus far, in countries such as Brazil, laws have not been sanctioned requiring the mandatory packaging with a protective cover for children:…”
Section: Discussionmentioning
confidence: 99%
“…Estudos da última década identificam potenciais em ações de prevenção 69 , mesmo que haja poucas evidênci-as de redução de injúrias através da utilização de meios como campanhas e doação de equipamentos de proteção [70][71][72][73] . As abordagens que reforçam a necessidade do papel ativo dos pais e responsáveis trouxeram resultados modestos na redução de injúrias 74 .…”
Section: Escorpionismounclassified
“…This included six RCTs (Baudier et al, 1988;Clamp & Kendrick, 1998;Colver, Hutchinson, & Judson, 1982;Gielen et al, 2007;Paul, Sanson-Fisher, & Redman, 1994;Watson et al, 2005) and one CBA (Schwarz, Grisso, Miles, Holmes, & Sutton, 1993), evaluating interventions providing safety education (OR 1.61, 95% CI 1.10À2.36 (Gielen et al, 2007)) and safety education plus equipment, with effect sizes ranging from RR 1.15 95% CI 1.03À1.28 (Clamp & Kendrick, 1998) to OR 14.30 95% CI 4.22À18.46 (Colver et al, 1982. The remaining 18 studies (see Table 4) evaluating a range of interventions including safety education, tailored safety education, safety education plus equipment found no significant difference in safe storage of medicines between treatment groups.…”
Section: Interventions Promoting Safe Storage Of Medicinesmentioning
confidence: 99%
“…Of the 31 primary studies, six reported significantly more intervention group families stored household and other products safely. Four RCTs (Colver et al, 1982;Hendrickson, 2002;Paul et al, 1994;Watson et al, 2005) provided safety education plus equipment and home safety inspections with effect sizes ranging from OR 1.31 95% CI 1.07À1.60 (Watson et al, 2005) to OR 15.79, 95% CI 4.65À53.62 (Hendrickson, 2005). One RCT provided safety education plus equipment (OR 2.21 95% CI 1.40À3.51 (Woolf et al, 1992)) and one RCT gave home safety counselling and safety equipment with specific injury focussed instructions in the ED prior to discharge (OR 2.58 95% CI 1.12À5.94) (Posner, Hawkins, GarciaEspana, & Durbin, 2004).…”
Section: Interventions Promoting Safe Storage Of Medicinesmentioning
confidence: 99%